PENGARUH KEJELASAN SASARAN ANGGARAN DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH DENGAN KINERJA MANAJERIAL SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA SATUAN KERJA PERANGKAT DAERAH KOTA PEKANBARU) - Anugerah, Riza Pramita; Taufik, Taufeni; Haryani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to examine : 1) The effect of budget objective clarity on performance accountability, 2) The effect of environmental uncertainly on performance accountability 3) The effect of budget objective clarity on performance accountability with managerial performance as moderating variable 4)The effect of environmental uncertainly on performance accountability with managerial performance as moderating variable. The population in this study is Regional Working Units (SKPD) at Pekanbaru. The selection of sample used purposive sampling method. Data that is used in this research is primary data, that was collected by survey techniques by distributing questionnaires to each functionary at 43 Pekanbaru’s SKPD. Moderated regression analysis was used as the method of analysis. The results showed that budget objective clarityhas positive significant effect on performance accountability because the tcount > ttable, , 2.457 > 1.989 with significant 0.015.Environmental uncertainly has negative significant effect on performance accountability because the tcount> ttable, 2.069 > 1.989 with significant 0.039. Managerial Performance variabel has significant score, 0.048 <0.05 , it means personal managerial performance moderate the relationship between budget objective clarity on performance accountability.Managerial Performancevariabel has significant score, 0.94 >0.05 , it means personal managerial performance not moderate the relationship between environmental uncertainly on performance accountabilityKeywords: budget, environtmental, performance, government performance, and managerial